Improving the Production Quality Processes at Bread SMEs in Jakarta - Fuji Rahayu; Desribeth Palullungan; Tasya Regina (Unusa Press, 2021)
The consumption pattern of the people in Indonesia is experiencing a shift. Consumption patterns that are influenced by socio-cultural factors today make people tend to consume food and drinks that are practical and easy to obtain. This pattern began in 2014 until now, making the percentage of food consumption increase by 2.5% per year. Bread is a finished food whose demand pattern has also increased. Due to the development of the middle-class population, an increase in the income of young people, and society's consumption pattern, which is increasingly shifting to a practical urban consumption pattern. The bread industry in Indonesia is still classified as the small and medium enterprises (SME) sector. Small and medium enterprises (SME) is a business sector with a significant impact on improving the economy in developing countries. The products are distributed to offices that work with bakeries and are sold in stores. This shows that the shop production must work quickly to meet consumer demand in the surrounding area. In fulfilling consumer demand, a production quality control process is required in the workstation to reduce defective products. This study aims to carry out a quality control process to reduce faulty products by using a control chart and the concept of kaizen to control and maintain the production process in bread SMEs so that quality and work effectiveness can be realized.